INNOVATIVE DEVELOPMENT OF THE FOREST INDUSTRY OF UKRAINE - MENDELA, Yevheniia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In modern business conditions, the effective development of any enterprise, industry, region, country is practically unreal without the introduction and use of innovations that determine the overall level of competitiveness of the business entity on the domestic and foreign markets. Attracting innovations can contribute to increasing the efficiency of the use of fixed and working capital, labor productivity, reducing the cost of production and other indicators, which contributes to reducing the cost of production, saving resources and achieving the target level of profit.Today, one of the main global directions of the innovative technological process is the development of forestry, the purpose of which is to improve and intensify activities through the use of the latest technologies. Therefore, the search for innovations that can increase the efficiency of forestry management is becoming more and more urgent. Forests are extremely important for the economic potential of Ukraine. They serve as raw materials for the activity and development of many branches of the economy, create favorable conditions for people's lives. Nevertheless, they are in a satisfactory state because there are many factors that stand in the way of their development. Therefore, research on the use of innovative technologies as a key to improving the efficiency of forestry activities requires in-depth research.The article comprehensively researches the implementation of innovative development of forestry in Ukraine, which is based on the concepts of sustainable development and forest management, using the best experience of European countries and traditions formed in Ukraine. The implementation of a number of innovative measures turned out to be a prerequisite for the successful development of national forestry. These measures are designed to eliminate contradictions between forestry and forestry, to develop an integrated process in the field of harvesting, conservation and use of forest resources based on lease relationships and common interests in organizations of sustainable forest use.The purpose of this article is to determine the main types of innovative technologies and their areas of application in the country's forestry.
Keywords: innovative development; forest industry; online monitoring; eco-paper; wooden house construction; ecological certification of forests